Provocative Methods of Non-Corrupt Consciousness Formation - N. V. Syuzeva (Образование и наука)
The paper is devoted to the necessity of using the provocative methods in pedagogy regarding them as the most effective ones in education focused on fighting the corruption. Both the social theory and human experience demonstrate that we have to change people’s consciousness and start it as early as possible in order to overcome corruption. The author takes the provocative therapy suggested by F. Farelli as the conceptual basis for the research, and considers the corruption phenomenon as the national disease that requires immediate treatment. The provocative methods can be used for identifying the corruption attitudes, emphasizing their irrational nature and getting rid of them. The paper describes the sequence of recommended stages of the above method application and gives some examples of pedagogic provocations. The author argues that pedagogic provocation is a perspective method stimulating personality development which requires further investigation and discussion.